Experimental Investigation on Behavior of Composite Open Web Steel Joists - Hadeed, Ali Farhan; Al-Hadithy, Laith Khalid; Aziz, Riyadh J. (Al-Nahrain Journal for Engineering Sciences, 2018)
The composite opened web steel joist supported floor systems have been common for many years. It is economic and has light weight and can embed the electrical conduit, ductwork and piping, eliminating the need for these to pass under the member, consequently eliminate the height between floors. In order to study the joist strength capacity under the various conditions, it had been fabricated seven joists composed of the steel and concrete slab connected to the top chord by shear connectors (headed studs). These joist have 2820 mm length c/c of the supports and 235 mm overall depth. In the present study, six variable parameters are adopted (Studs distribution, Degree of shear connection, Degree of the web inclination, Shape of the web, Density of concrete for slab and length of the shear connector). The test results exhibited that minimum strength capacity was 160kN for light weight joist and maximum capacity was 225kN for joist of long shear connectors at failure. The results were compared by ultimate flexural model by Azmi.